Invasive candidiasis in children - N. N. Klimko; O. P. Kozlova (Журнал инфектологии)
The prevalence of invasive candidiasis (IC) in pediatric hospitals is from 4,3 to 15,2 per 10,000 hospitalized, in ICU – from 3,5 to 7 cases per 1,000, with HSCT – 2,9%. The average length of stay of a patient in the hospital before the development of IC varies from 21 to 56 days, in the ICU – more than 15 days. Knowledge of risk factors (ICU stay for ≥15 days, use of antibacterial drugs and parenteral nutrition, active malignant neoplasm, etc.) makes it possible to identify patients with a high (10-46%) risk of developing IC. Candida albicans remains the leading causative agent of IC in children, but infections with non-albicans Candida spp. have increased and an increase in the resistance of IC pathogens to azole antimycotics was noted. The main clinical variant of IC in children is candidemia, other forms include the central nervous system, abdominal organs, eyes, heart, bones and joints, kidneys, skin and subcutaneous tissue involvement, as well as chronic disseminated (hepatolienal) candidiasis. Blood culture, the main method of laboratory diagnostics of IC, is characterized by low sensitivity and requires a long time. Methods of noncultural diagnostics of IC (1,3-β-D-glucan, mannan and antimannan antibodies, T2 Candida etc) in children have not been sufficiently studied. The main drugs for the treatment of IC in children are echinocandins (anidulafungin, etc.), and CVC removal/replacement is necessary. The overall mortality rate in pediatric patients within 30 days after the diagnosis of IC is 37% to 44%.